A dual-process perspective to explore decision making in internet gaming disorder: An ERP study of comparison with recreational game users. (March 2022) - Zhou, Yuhong; Yao, Mengyun; Fang, Shuting; Gao, Xuemei
Abstract: Existing internet gaming disorder (IGD)-related research has focused on impulsive and control systems separately, with little research conducted to explicitly explore these two systems simultaneously from a comprehensive perspective (i.e., the dual process model). To address this question, the current study used event-related potentials (ERPs) to record brain activity in individuals with IGD and recreational game users (RGU) during decision making tasks. Results showed no between-groups differences, both at the behavioral and neural levels, except for the P2 component. During discount processing, larger P2 amplitudes were found in RGU subjects; and RGU displayed larger P3 amplitudes in short- and long-term delays, whereas no delay main effect was found in IGD subjects. During risk-taking, RGU subjects showed larger N2 amplitudes for risk disadvantageous (RD) in the loss domain than the gain domain, whereas the IGD group did not exhibit any difference across domain. These results suggest that IGD subjects did not differ from RGU subjects in impulsive and control systems. However, neural differences between IGD and RGU subjects were observed under different decision-making conditions, suggesting that IGD may be related to altered realistic reward preference and reduced loss aversion, as well as to less effortful decision assessment. Highlights: No significant differences in the dual-process systems both at behavioral and neural levels between IGD and RGU subjects. The RGU rather than IGD subjects utilized more executive control resources when experiencing adverse losses. More cognitive resources were recuited to weigh immediate against delayed rewards in RGU rather than in IGD subjects. The RGU subjects showed increased sensitivity toward realistic rewards when compared with IGD subjects.